The Role of Customer Insight in Enhancing the Strategic Foresight in The Iraqi Organizations - Al-Taie, Yousef H.; Shaaban, Abdul-Karim Hadi (International Journal of Psychosocial Rehabilitation, 2020)
This paper seeks to explore the importance of reading customer insight by the marketing managers in Iraqi organizations in improving the competitive advantage. In addition, it aims to identify the level of strategic foresight for marketing managers in these organizations. The paper also seeks to test the relationship between customer insight and the strategic foresight for marketing managers in Iraqi organizations. The paper uses a quantitative research method using a questionnaire distributed to a sample of marketing managers in Iraqi Organizations. The results show that there is a strong and statistically significant correlation between the variable of customer insight and the future foresight variable. The detailed results also show that there is a strong positive correlation between customer insight with all dimensions (customer passion, destroying need, product regeneration, and proactive orientation) and strategic foresight to marketing managers.